Cell biology, biophysics, and mechanobiology: From the basics to Clinics - Zeng, Y. (Cellular and Molecular Biology, 2017)
Cell biology, biomechanics and biophysics are the key subjects that guide our understanding in diverse areas of tissue growth, development, remodeling and homeostasis. Novel discoveries such as molecular mechanism, and mechanobiological mechanism in cell biology, biomechanics and biophysics play essential roles in our understanding of the pathogenesis of various human diseases, as well as in designing the treatment of these diseases. In addition, studies in these areas will also facilitate early diagnostics of human diseases, such as cardiovascular diseases and cancer. In this special issue, we collected 10 original research articles and 1 review...